Verification of Management Support of Professional and Educational Trajectory of Students in Terms of Socio-Cultural Educational Environment of University - N. V. Tsytulina; N. L. Sokolova; M. G. Sergeyeva (Научный диалог)
The verification of management support of professional and educational trajectory of students in terms of socio-cultural educational environment of the university is considered. The research urgency is caused by the transition to the educational standards of the third generation, which offer students and teachers new opportunities. The teachers face the challenge not only of transferring knowledge and skills to students, but also the formation of future graduate’s personality, capable of professional development. The article analyses the conditions for the maintenance of professional and educational trajectory of students at the university. Professional motives and commitment to professional development of students, the level of professional knowledge, commitment to their completion and perfection during the period of professionalization of personality are commented. Formed abilities and skills, professional experience are represented as a set of indicators of quality of professional and personal development of students. The authors hold the view that in practice of higher education institutions the teaching staff faces the task of the organization and ensuring educational process with the guarantee of student’s transition to higher levels of professional and personal development. It is proved that the requirements of vocational and educational trajectory allows to approximate the educational process to the needs of students, to form their professional and educational development in the conditions of the university, to prepare for practice.